Puitika Kesepian Dalam Kitab Puisi Perihal Gendis Karya Sapardi Djoko Damono - Lailatus Sholihah (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This study aims to (1) analyze the patterns of character-narrator development and (2) know the psychological of Gendis figures that are built in the anthology of poetry Perihal Gendis. This study uses qualitative research methods based on the literature on the anthology of poetry Perihal Gendis written by Damono (20018). This study uses (1) the theory of rhetorical figures by Gerard Genette which was later developed by Culler to find out the narrative structure and (2) theory of psychoanalysis by Sigmund Freud to find out the psychological condition of Gendis. The results of this study can be seen through the patterns of character and narrator development in poetry which are (1) "Why are you so mean/leave me alone?", (2) "Silent Gendis", (3) "People say" and (4) "Turning the Keys to the House. Furthermore, the psychological condition of Gendis in the text can be found in poetry (1)"No Need" and (2)" Sitting on the Back Porch of the Full Moon. Overall, it can be seen that the departure of Gendis’ father and mother evoke a moment of Gendis' image with living things, things around them, and the soul of Gendis who deeply feels loneliness.